Nude mutation influences limb skeletal muscle development. - Morrison, J; Partridge, T; Bou-Gharios, G (2005)
The nude mouse lacks functional T cells and other skin defects due to the absence of Foxn1 transcription factor. The mdx mouse bred onto a nude background (Foxn1-/-), to generate mdx nu/nu, serves as a valuable model for the use in muscle cell transplantation or gene therapy studies, to avoid a detrimental immune response. However, it has been shown previously that the mdx nu/nu mice have a skeletal muscle specific alteration in collagen production, which in the case of the limb muscles acts at or before the onset of the disease. This led to the conclusion that the nude mutation has an effect on the collagen deposition in skeletal muscles, which may be acting in a T cell independent manner. In an attempt to elucidate the role of the nude mutation on collagen production in skeletal muscles, we have measured collagen levels in several muscles of C57BL/10 nu/nu mice and compared them with mdx nu/nu and Foxn1+/+ control mice. We report here that the limb muscles of the young C57BL/10 nu/nu and mdx nu/nu mice contained a far higher proportion of collagen at an early age than Foxn1+/- control mice but regained normal levels by 12 weeks of age. This was largely attributable to the fact that 3 weeks old nude mice had considerably smaller limb muscles than Foxn1+/- mice which subsequently grew to normal size. We conclude that the nude mutation retards the early growth of development of muscle but not of the matrix tissue in limb muscles.